The Effect of Benefits, Convenience, Risk, Income on Purchase Decisions Using Shopee Paylater - Jimmy Daniel Aprianto; Baruna Hadibrata (Dinasti Publisher, 2023)
A new digital payment system was developed as a result of the rapid development of technology and the internet in Indonesia. Financial technology (fintech) is one of the technological advances in the increasingly widespread Indonesian financial sector. The research was conducted with the aim of analyzing the relationship between perceived benefits, perceived convenience, risk, and income on purchasing decisions using a shopee paylater. The research model uses a causal research design. The population in this study are all customers who use the Shopee Paylater application in DKI Jakarta whose exact location is unknown. The technique used in selecting the sample is purposive sampling. By determining the criteria data, characteristics, and appropriate characteristics. The minimum number of samples in this study is 135 respondents. Researchers used IBM SPSS Statistics 26 software to analyze descriptive characteristics and SmartPLS 3.3 software to measure research data using the Partial Least Square (PLS) method. The results show that benefits and convenience have a positive and significant effect on purchasing decisions. However, risk and income have a positive but not significant effect on purchasing decisions